Effect size reporting among prominent health journals: a case study of odds ratios. Issue 4 (10th December 2020) - Chu, Brian; Liu, Michael; Leas, Eric C; Althouse, Benjamin M; Ayers, John W
Abstract : Background: The accuracy of statistical reporting that informs medical and public health practice has generated extensive debate, but no studies have evaluated the frequency or accuracy of effect size (the magnitude of change in outcome as a function of change in predictor) reporting in prominent health journals. Objective: To evaluate effect size reporting practices in prominent health journals using the case study of ORs. Design: Articles published in the American Journal of Public Health ( AJPH ), Journal of the American Medical Association ( JAMA ), New England Journal of Medicine ( NEJM ) and PLOS One from 1 January 2010 through 31 December 2019 mentioning the term 'odds ratio' in all searchable fields were obtained using PubMed. One hundred randomly selected articles that reported original research using ORs were sampled per journal for in-depth analysis. Main outcomes and measures: We report prevalence of articles using ORs, reporting effect sizes from ORs (reporting the magnitude of change in outcome as a function of change in predictor) and reporting correct effect sizes. Results: The proportion of articles using ORs in the past decade declined in JAMA and AJPH, remained similar in NEJM and increased in PLOS One, with 6124 articles in total. Twenty-four per cent (95% CI 20% to 28%) of articles reported the at least one effect size arising from an OR. Among articles reporting any effect size, 57% (95% CI 47% to 67%) did so incorrectly. Taken together, 10% (95% CI 7% to 13%) of articles included a correct effect size interpretation of an OR. Articles that used ORs in AJPH more frequently reported the effect size (36%, 95% CI 27% to 45%), when compared with NEJM (26%, 95% CI 17.5% to 34.7%), PLOS One (22%, 95% CI 13.9% to 30.2%) and JAMA (10%, 95% CI 3.9% to 16.0%), but the probability of a correct interpretation did not statistically differ between the four journals (χ 2 =0.56, p=0.90). Conclusions: Articles that used ORs in prominent journals frequently omitted presenting the effect size of their predictor variables. When reported, the presented effect size was usually incorrect. When used, ORs should be paired with accurate effect size interpretations. New editorial and research reporting standards to improve effect size reporting and its accuracy should be considered.